2020
DOI: 10.1111/apa.15575
|View full text |Cite
|
Sign up to set email alerts
|

Rates and risk factors of severe respiratory syncytial virus infection in 2008‐2016 compared with 1986‐1998

Abstract: Aim Since the introduction in 1979 of rapid testing using immunofluorescence, we have collected information about children hospitalised for confirmed respiratory syncytial virus (RSV) infection in the northern Stockholm area. We here report hospitalisation rates, risk factors and complications in 2008‐2016 compared with 1986‐1998. Methods Microbiological laboratory reports and retrospective chart review. Comparison of the two periods was complicated by changing testing routines, with a more sensitive method an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…In 2008–2016, there were 400 admissions/100 000 person‐years in children under the age of 5 years in Stockholm and the highest rate was in infants below 1 year of age. Children with underlying conditions were overrepresented among admitted cases in a previous study that included the RSV case group in the present study 12 . Internationally, RSV admissions have been linked to underlying chronic conditions, crowding, having lots of siblings, low socio‐economic status and a low educational level of parents 13 .…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…In 2008–2016, there were 400 admissions/100 000 person‐years in children under the age of 5 years in Stockholm and the highest rate was in infants below 1 year of age. Children with underlying conditions were overrepresented among admitted cases in a previous study that included the RSV case group in the present study 12 . Internationally, RSV admissions have been linked to underlying chronic conditions, crowding, having lots of siblings, low socio‐economic status and a low educational level of parents 13 .…”
Section: Introductionmentioning
confidence: 61%
“…We previously showed that RSV infections are increasingly diagnosed in older children with medical risk factors, partly due to multiple-agent PCR tests. 12 The proportion of chickenpox cases with a chronic condition was also high, but as the case numbers were low, we could not establish this statistically. Children with influenza, RSV or chickenpox were more likely to be admitted to the PICU than rotavirus cases.…”
Section: The Northern Stockholm Populationmentioning
confidence: 91%
See 2 more Smart Citations
“…The study is limited by its retrospective design, with few clinical variables available, and results may be influenced by unmeasured confounders. In particular, caution should be taken in interpreting results for children with comorbidities predisposing for severe disease, as this is a heterogeneous group with varying degrees of disease severity and often multiple factors that may interact [2,8,42,43]. Studies assessing risk factors for major medical interventions in children with VLRTI often exclude high-risk groups from the analysis [24,38,44].…”
Section: Discussionmentioning
confidence: 99%